A cruz vencerá o comunismo : o discurso anticomunista do Jornal Folha do Norte do Paraná (1962-1965) - Brito, Angélica (2015)
Current research discusses the anticommunist discourse of the newspaper Folha do Norte do Paraná between 1962 and 1965. The Catholic newspaper started publication in Maringá PR Brazil in 1962 and was read in several town and cities of the state of Paraná till the end of its issues in 1979. The representations of communism disseminated by the newspaper in the early 1960s require an analysis of the international and regional political situation. There will be a constant dialogue with the historical issues analyzed throughout this study. The issues underscored in current analysis comprise the political and ideological polarization of the Cold War, the intense anticommunist campaign against the Goulart administration, the stance of the Catholic Church in the wake of communism and the general conflicts around the trade-unionization of rural workers in the northern region of the state of Paraná. The A Folha do Norte do Paraná, similar to other Brazilian newspapers, disseminated representations that contributed towards the consolidation of the country´s anticommunist imaginary. Without shunning the variants within a wider stance, the facts of regional history that registered the characteristics of the struggle against the "Red threat" in the region are underscored.